Pengaruh Kompensasi, Budaya Organisasi dan Kepuasan Kerja Terhadap Kinerja (Studi pada Aparatur Sipil Negara Kecamatan Argomulyo Kota Salatiga) - Ningrum, Ryan Widya; Sugiarto, Agus (Ekonomis: Journal of Economics and Business, 2024)
This research aims to determine the influence of compensation factors, organizational culture and job satisfaction on ASN performance simultaneously and partially in Argomulyo District, Salatiga City. This research uses quantitative methods with data collection techniques through distributing questionnaires to all State Civil Apparatus in the Argomulyo Salatiga District, totaling 71 people. The sampling technique used is a saturated sample. The data analysis used is multiple linear regression analysis. The results of this research conclude that partial compensation factors have no effect on ASN performance. However, organizational culture and job satisfaction influence ASN performance. Meanwhile, simultaneously all of these variables influence the performance of ASN in the Argomulyo Salatiga District.